Building an Application that reads Secure Information Stored on the Chip of the Citizen Identity Card in Vietnam - Le, Van-Hoan; Luc, Nhu-Quynh; Dao, Toan Thanh; Do, Quang-Trung (Engineering, Technology & Applied Science Research, 2023)
Reading the information on the CIC/passport is very meaningful in serving the life activities of citizens in Vietnam and of foreign citizens visiting Vietnam. This research is based on the operating modes, such as BAC, FACE, and EAC to read the data contained in the chip put on the Citizen Identity Card (CIC) out securely. Specifically, the authors used the BAC mode to perform safe data reading from the CIC’s chip. BAC mode uses 3DES and SHA1 algorithms to encrypt data to ensure security, so when the data are transmitted from the chip they are encrypted and decryption is performed by the application. In this paper, a complete application has been built for reading personal information stored securely on CIC. This application is built based on the BAC reading mode corresponding to CIC in Vietnam and meets the requirements of the ICAO 9303 standard, so it is able to read passports or CICs of other countries that use this standard. The performance of this application when reading data stored on fields DG1, DG2, and DG13 is improved with a speed of about 1.2s - 1.3s for all 3 data fields.